Access to Fertility Services for Lesbian, Bisexual, or Pansexual Women and Queer, Trans, or Non-Binary People: A Rapid Review of the Scientific Literature - Côté, Isabel; Fournier, Claudia; Aslett, Anna; Lavoie, Kévin (Science of Nursing and Health Practices, 2024)
Introduction: Lesbian, bisexual, and pansexual (LBP) women as well as transgender, queer, and non-binary individuals (TQNB) often rely on medically assisted reproduction (MAR) to build their families, but do not always have access to these services. Currently, there appears to be no literature that comprehensively reviews, from an ecosystemic perspective, the main factors determining LBP women's and TQNB people's access to MAR. Objective: This rapid review aims to identify, from an ecosystemic perspective, the factors described in the scientific literature as influencing LBP women's and TQNB people's access to MAR. Methods: A literature search using 11 search engines identified 22 articles presenting results of recent empirical studies (2018-2023) using various methodologies. Relevant results were subjected to thematic analysis, and identified factors were classified within an ecosystemic model. Results: The identified factors are (1) at the microsystemic level, support from the social network and healthcare personnel; (2) at the exosystemic level, healthcare personnel's awareness of sexual and gender diversity, adequacy of information and documentation, organizational logic of fertility services, cost of services, legislation; (3) at the macrosystemic level, heterocisnormativity as a cross-cutting influence. Discussion and conclusion: To ensure access to MAR for LBP women and TQNB people, a comprehensive and multi-level approach is necessary. Suggestions for health practices and public policies are proposed.